TECHNO-ECONOMIC ANALYSIS OF GASIFICATION TECHNOLOGY WITH VARIOUS TYPES OF BIOMASS IN MOBILE BIOMASS GASIFIER P2 - Rizky Pradana, Muhammad (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
The purpose of this study is to determine the value of LCOE for gasification systems with several types of biomass fuel, to know the economic feasibility of gasification systems with several biomass fuels, and to know the most economical type of biomass to be used as Mobile Biomass Gasifier P2 fuel. The research methods used in this study include quantitative approaches and several stages of research. The stages of research consist of the formulation of the problem, where the research problem is identified and formulated to determine the methods and analysis to be used. This research resulted in bagasse being the most economical biomass choice with an LCOE value of Rp 1,050.17/kWh, followed by cotton waste, straw, corn cobs, and rice husks. In addition, gasifier systems with bagasse biomass also show good economic feasibility based on NPV, IRR, PBP, and BCR parameters.